The Effect Of Work Discipline And Work Environment On Employee Performance Through Organizational Citizenship Behaviour (Ocb) As A Mediating Variable At The Regional Special Hospital Of Maluku Province - Brian A. Tetelepta; Conchita V Latupapua; Agustina Risambessy (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research was conducted to obtain an explanation regarding the influence of work discipline and work environment on employee performance through Organizational Citizenship Behavior (OCB) as a mediating variable at the Maluku Province Regional Special Hospital. The purpose of this research is to analyze the influence of work discipline and work environment on employee performance and the role of organizational citizenship behavior (OCB) as a mediating variable. This research uses quantitative research. This research uses smartPLS version 4 software, the data collection instrument is a questionnaire measured using a Likert scale. This study had a sample of 100 respondents, namely employees of the Maluku Province Regional Special Hospital. The results of this research show that Work Discipline has no significant effect on employee performance with a p value of 0.709 > 0.05, the Work Environment has a significant effect on Employee Performance with a p value of 0.000 < 0.05, Organizational Citizenship Behavior has no significant effect on Employee Performance with a p value of 0.358 > 0.05, Work Discipline has a significant effect on Organizational Citizenship Behavior with a p value of 0.000 < 0.05, Work Environment has a significant effect on Organizational Citizenship Behavior with a p value of 0.000 < 0.05, Organizational Citizenship Behavior does not mediate between Work Discipline and Employee Performance with a p value 0.378 > 0.05, Organizational Citizenship Behavior does not mediate between the Work Environment and Employee Performance at the Regional Special Hospital of Maluku Province.